Studi Tutupan dan Kerapatan Lamun di Pantai Pandaratan Kabupaten Tapanuli Tengah Provinsi Sumatera Utara - Wawan Wajuna; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Pandaratan Beach has seagrass ecosystem which able to adaptation in water with high salinity.The research aims to determined species, coverage and density of seagrass at Pandaratan Beach.The research was conducted in Pandaratan Beach, Sarudik Subdistrict, Central Tapanuli Regency, North Sumatera Province from March until April 2018. The method of this research was purposive sampling which has three stations. The result of this research consists of two species of seagrass, Enhalus acoroides and Cymodocea rotundata.Precentage for seeagrass coverage at all stations were 34,47%, 20,27% and 25,38% with average value 26,70% which categorized in medium class. The values for seagrass density of Enhalus acoroides at first station until third station are 389 ind/m2, 72 ind/m2 and 85 ind/m2 with average value 182 ind/m2. The values for seagrass density of Cymodocea rotundata at first station until third station are 54 ind/m2, 127 ind/m2 and 260 ind/m2 with average value 147 ind/m2. The value of dispersial pattern for Enhalus acoroides is -0,057 and the value for Cymodocea rotundata is-0,601 both of seagrass species was categorized in equable class. The sedimentation rate was categorized in medium class with value for each station were 12,5 mg/cm3/day, 36,3 mg/cm3/day and 27,7 mg/cm3/day.Keywords ; Seagrass, Coverage, Density, Dispersial Pattern, Sedimentation Rate, Pandaratan Beach